PENGARUH PROFITABILITAS,STRUKTUR AKTIVA, DAN PERTUMBUHAN AKTIVA TERHADAP KEBIJAKAN HUTANG JANGKA PANJANG (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2008-2011) - Purnaningrum, Iudiarti; Djawahir, Achmad Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Selection source of financing is an important decision that should be considered by company. One of the sources financing that can be chosen is long-term debt. In deciding the policy of long-term debt, the company should consider it appropriately. In 2011 food and beverage company listed on the Stock Exchange, increase the use of long-term debt. Related with the theory of capital structure, it is necessary to study the effect of profitability, asset structure and asset growth towards long-term debt policy. This study aims to identify and analyze the effect of profitability, asset structure and asset growth towards long-term debt policy on food and beverage company listed on the Stock Exchange over period 2008-2011. The population amounts to 12 companies. The samples used in this study is the entire population. The method of analysis used in this study is multiple linear regression analysis. The analysis begins with the classical assumption that consist of autocorrelation test, normality test, multicollinearity test, and heteroscedasticity test. After that, the F-test to determine the effect of simultaneous, t-test to determine the effect of partial and dominant test to determine the dominant variable. The results of the F test analysis showed that simultaneously the profitability, asset structure and assets growth influence long-term debt policy. T test analysis showed that the profitability has significant effect and negative relationship with long-term debt. While the asset structure of and asset growth have significant effect and positive relationship with long-term debt. The dominant test results show that the profitability dominant influence the of long-term debt policy. Keywords: long-term debt policy, profitability, asset structure, asset growth